Migration in Sweden and Finland 1613–1618 (from Älvsborg's ransom taxation records) - Andersson, Martin (Södertörn University, 2023)
Data on migration (local as well as interregional and international) in Sweden and Finland during the period 1613–1618. The data concern the household/individual level, urban and rural. For each household/individual the data contain title/occupation, name, home address, and migration destination; given as parish/town, hundred, and county/country (if the data is present in the source). The data is collected from the taxation records from the second Älvsborg's ransom taxation (in the National Archives of Sweden and Finland).

Uppgifter om migration (såväl lokal som interregional och internationell) i Sverige och Finland under åren 1613–1618. Uppgifterna är på hushålls- eller individnivå och rör såväl landsbygd som städer. För varje hushåll/individ anges (i den mån det uppges i källan) titel/yrke, namn, ursprungsort samt destination för migrationen (angivet med socken/stad, härad och landskap/land). Uppgifterna är hämtade från rannsakningslängderna från Älvsborgs andra lösen (i Riksarkiven i Stockholm och Helsingfors).
Migration i Sverige och Finland 1613–1618 (från Älvsborgs lösen)
Keywords: MIGRATION (HUMAN); MIGRATION; demographic history; befolkningshistoria; Migration; Migration; HISTORY; HISTORIA; History; Historia